Combination of red cell distribution width and American Society of Anesthesiologists score for hip fracture mortality prediction. Issue 6 (June 2016) - Yin, P.; Lv, H.; Zhang, L.; Long, A.; Zhang, L.; Tang, P.
Abstract Summary The prognostic value of red cell distribution width (RDW) and a combination of RDW and the American Society of Anesthesiologists (ASA) score for long-term hip fracture mortality remains unknown. Our data showed that both RDW and ASA were independent risk predictors. A combination of these two parameters may provide a more powerful strategy for the prediction of hip fracture mortality. Introduction Red cell distribution width (RDW) has recently been suggested as an independent predictor of prognosis in a variety of disorders. The American Society of Anesthesiologists (ASA) system has been widely used to stratify patients for outcome evaluations. However, the prognostic value of RDW and a combination of RDW and the ASA score for long-term hip fracture mortality has yet to be studied. Methods This prospective cohort study included 1402 subjects from 2000 to 2011 with a follow-up study over a 2 year period. Cox proportional hazards models with a bootstrap validation were used to evaluate associations of RDW, ASA, and a combination of both with long-term mortality. The global fit and the area under the receiver operating characteristic (ROC) curve (AUC) for model discrimination were further analyzed. Results Both RDW and ASA exhibited as independent risk predictors of 2-year mortality. The population with elevation of either RDW or ASA increased the risk of mortality (bootstrap validated hazard ratio (HR) 1.971 95 % confidence interval (CI) [1.336–3.005]p  < 0.01) while those with an increase in both assessments (bootstrap validated HR 2.667 95 % CI [1.526–4.515]p  < 0.01) were at the highest risk for mortality. The addition of the combination of ASA and RDW improved the discrimination power of risk prediction models (AUC increased from 0.700 to 0.723, p  < 0.05). Conclusion Both RDW and ASA exhibited as independent risk predictors of 2-year hip fracture mortality. The combination of these two readily available parameters may provide a more powerful and effective strategy for the assessment of all-cause mortality in hip fracture patients.